Analysis of the profile of patients with acne vulgaris who are seen at the dermatology office (Research, Society and Development, 2022)
Objective: To identify the profile of patients with acne vulgaris who seek care at the Dermatology Office from January to November 2021. Methodology: This is a descriptive and cross-sectional study with a quantitative approach. The sample consisted of 313 patients. The collected data were initially registered in the Microsoft Excel version 2010 Windows spreadsheet. The tabulation and performance of statistical tests were performed using the IBM SPSS Statistcs 20.0 program. Results: The profile of patients with acne, most of them are female, aged approximately 18 to 20 years, with moderate inflammatory acne, who remained under treatment with Isotretinoin and contraceptives, the quality of life of the interviewed patients was not in agreement. with the literature, so that it presented rates of patients with acne critically low when compared to the rates of the population without acne. Conclusion: This study allowed us to identify the profile of individuals with acne vulgaris seen in an office. Acne is a high-incidence pathology that can have a significant psychological impact, especially in the highest degrees of severity.